Anti-allergic actions of a Chinese patent medicine, huoxiangzhengqi oral liquid, in RBL-2H3 cells and in mice - Jianbin Sun; Sixing Huang; Yao Qin; Ping Zhang; Ziwei Li; Li Zhang; Xin Wang; Ruijun Wu; Shaorong Qin; Jiayong Huo; Kunquan Xiao; Weizao Luo (Taylor & Francis Group, 2021)
Context Huoxiangzhengqi oral liquid (HXZQ-OL), a traditional Chinese medicine formula, has antibacterial, anti-inflammation and gastrointestinal motility regulation effects. Objective The study investigates the anti-allergic activity and underlying mechanism of HXZQ-OL. Materials and methods IgE/Ag-mediated RBL-2H3 cells were used to evaluate the anti-allergic activity of HXZQ-OL (43.97, 439.7 and 4397 μg/mL) in vitro. The release of cytokines and eicosanoids were quantified using ELISA. RT-qPCR was used to measure the gene expression of cytokines. The level of intracellular Ca2+ was measured with Fluo 3/AM. Immunoblotting analysis was performed to investigate the mechanism of HXZQ-OL. In the passive cutaneous anaphylaxis (PCA), BALB/c mice (5 mice/group) were orally administrated with HXZQ-OL (263.8, 527.6 and 1055 mg/kg/d) or dexamethasone (5 mg/kg/d, positive control) for seven consecutive days. Results HXZQ-OL not only inhibited degranulation of mast cells (IC50, 123 μg/mL), but also inhibited the generation and secretion of IL-4 (IC50, 171.4 μg/mL), TNF-α (IC50, 88.4 μg/mL), LTC4 (IC50, 52.9 μg/mL) and PGD2 (IC50, 195.8 μg/mL). Moreover, HXZQ-OL suppressed the expression of IL-4 and TNF-α mRNA, as well as the phosphorylation of Fyn, Lyn and multiple downstream signalling proteins including MAPK and PI3K/NF-κB pathways. In addition, HXZQ-OL (527.5 mg/kg) attenuated the IgE-mediated PCA with 55% suppression of Evans blue exudation in mice. Conclusions HXZQ-OL attenuated the activation of mast cell and PCA. Therefore, HXZQ-OL might be used as an alternative treatment for allergic diseases.